(untitled) (Journal of the College of Basic Education, 2025)
One of the most special connections between the servant and his Lord is the divine mercy, which was represented by Islam, which emerged at dawn, bestowing upon humanity light that removed darkness and injustice, at the hands of the Messenger of Mercy, MuhammadThe Almighty said: ( And We have not sent you except as a mercy to the worlds). And from it emerged the title of the departed nation as a title, so that you may be a starting point. For the values ​​of all humanity, and a light that guides to what is best, to be associated with good deeds, forgiveness, and divine pardon that is relentless toward eternal paradise. Therefore, my research was in which I unveiled the meanings of divine mercy, its concept, and its connotations in the Holy Qur’an in general, and in Surat Al-Kahf in particular. Our hearing may hear some words that come with the meaning of mercy, in which the Qur’an has changed the explicit wording of mercy, in which there is a special indication of the meaning that does not fit with the context, such that the word mercy does not replace it. It is one of the rhetorical miracles of the Qur’an, as the words in the Book of God never replace one another, as their indication of what is intended is more eloquent and eloquent than their counterparts. The concept of mercy is stated in language as indicating kindness, tenderness, compassion, and gentleness, and mercy and mercy come in the meaning of mercy, and the truth is that if mercy is its principle in the heart and the turning of the soul requires it to forgiveness and benevolence, It is not just a psychological emotion that has no effect on the outside, but rather its effects and manifestations have been embodied in the world of martyrdom, represented by pardoning the one who committed a transgression, relieving the distressed, feeding the hungry, and other forms of mercy and humanity. In terminology, scholars said that it is a state of conscience that afflicts the one who has tenderness of heart, achieving benevolence after his psychological turn to it. I included in my research the analogues of mercy after examining the verses of mercy in the Holy Qur’an and books of interpretation, and I found it in several aspects, the most prominent of which are: prophecy, the Qur’an, heaven, infallibility, intercession, reward and reward, grace and sustenance, abundance, victory, compassion and tenderness, answering prayers, affection, and success, and each of them has its indication of divine mercy in the Holy Qur’an. Then I moved to Surat Al-Kahf specifically, and explained the number of its verses, their differences and virtues, and their interpretation. Then I began to embody the meanings of mercy in it, meaning and verbally. Then I concluded it with the most important results that I reached, then mentioned the sources that were numerous as required by this research, and with the last line, I thank God Almighty who enabled me to do this research, asking Him Almighty for acceptance and payment.